Contrasting continuous emission versus freeze-out via HDT - Padula, S. S.; Grassi, F.; Hama, Y.; Socolowski, O. (World Scientific Publ Co Pte Ltd, 2001)
The effect of continuous emission hypothesis on the two-pion Bose-Einstein correlation is discussed and compared with the corresponding results based on the usual freeze-out ansatz. Sizable differences in the correlation function are observed when comparing these two scenarios of the decoupling process. They could lead to entirely different interpretation of properties of the hot matter formed in high-energy heavy-ion collisions.